EGFR mutant locally advanced non-small cell lung cancer is at increased risk of brain metastasis. (September 2019) - Mitra, Devarati; Chen, Yu-Hui; Li, Richard; Hermann, Gretchen; Atkins, Katelyn; Kozono, David; Baldini, Elizabeth H.; Aizer, Ayal; Chukwueke, Ugonma; Mak, Raymond H.
Highlights: Locally advanced EGFR+ NSCLC patients have a high likelihood of brain metastasis. The high likelihood of EGFR+ brain metastasis is independent of survival duration. Surveillance MRI may allow early identification and treatment of brain metastasis. Abstract: Background and purpose: Small studies of primarily metastatic non-small cell lung cancer (NSCLC) have suggested an association between EGFR mutation (EGFR+) and likelihood of brain metastasis. However, these studies are confounded by follow-up time bias. We performed a competing risk analysis of brain metastasis in a more uniform locally advanced NSCLC (LA-NSCLC) cohort with known tumor genotype. Materials and methods: Between 2002 and 2014, 255 patients with LA-NSCLC underwent tumor genotyping for EGFR, ALK and/or KRAS (180 patients had follow-up brain imaging). Cumulative incidence and Fine-Gray regression were performed on clinical variables including genotype and risk of brain metastasis, with death as a competing event. Results: The proportion of tumors with aberrations in EGFR, ALK and KRAS were 17%, 4% and 28%, respectively. The median follow-up was 68 months. On multivariate analysis, EGFR+ was significantly associated with risk of brain metastasis in the full patient cohort (HR 2.04, 95% CI 1.22–3.39, p = 0.006) as well as in the subset of patients with brain follow-up imaging (HR 1.91. 95% CI 1.17–3.13, p = 0.01). This translated to a higher cumulative incidence of brain metastasis in EGFR+ patients at 3 and 5 years (33.3% vs. 23.2 and 43.8% vs. 24.2%, p = 0.006). Conclusion: Patients with EGFR+ LA-NSCLC have a significantly higher likelihood of developing brain metastasis after standard combined modality therapy, independent of their longer overall survival. This high-risk genotypic subgroup may benefit from routine surveillance with brain MRI to allow early salvage with targeted systemic- and/or radiation-therapies.